An Extended Hypofractionated Palliative Radiotherapy Regimen for Head and Neck Carcinomas - Michael Laursen (Frontiers in Oncology, 2018)
BackgroundPalliative radiotherapy to patients with head and neck cancer is often necessary, but there is a substantial variation in the treatment regimens reported in the literature, and consensus on the most appropriate schedules does not exist. In order to minimize acute toxicity while at the same time trying to achieve prolonged tumor control, a long hypofractionated regimen has been used routinely in Denmark. In the current retrospective study, we investigated the outcome in patients intended for palliative radiotherapy with this regimen.Materials and methodsPatients with newly diagnosed head and neck cancer treated with palliative radiotherapy of 52–56 Gy in 13–14 fractions twice weekly from 2009 to 2014 were included. Patients were excluded if they had previously received radiotherapy. Data on disease location, stage, patient performance status (PS), treatment response, acute skin and mucosal toxicity, and late fibrosis were collected prospectively and supplemented with information from medical records.Results77 patients were included in the study. Fifty-eight patients (75%) completed the intended treatment. Loco-regional tumor response (complete or partial) was evaluated 2 months posttreatment and observed in 45% of the entire population corresponding to 71% of patients alive. PS had a significant influence on survival (p = 0.007) and on not completing the intended treatment. Grade III or IV acute mucositis were observed in 25%, and grade III or IV acute dermatitis observed in 15%.ConclusionPalliative hypofractionated radiotherapy with 52–56 Gy in 13–14 fractions shows good tumor response and tolerability in a vulnerable patient population. However, it may not be suited for patients in poor PS.